Evaluation of plasma glucagon-like peptide-2 in dogs with chronic enteropathies - Riehm, Michelle Deanna (Kansas State University, 2023)
The enteroendocrine hormone glucagon-like peptide-2 (GLP-2) promotes gastrointestinal mucosal growth and healing in response to injury or disease. In humans with inflammatory and malabsorptive enteropathies, mucosal damage impacts GLP-2 secretion, with effects dependent on disease severity. In dogs with idiopathic chronic enteropathies, similar histopathological and biochemical changes to those observed in humans are noted. Glucagon-like peptide-2 has yet to be evaluated in dogs with chronic enteropathies. A prospective study was performed to compare fasting and post-prandial plasma GLP-2 concentrations in dogs with uncontrolled chronic enteropathies to healthy dogs, with the hypothesis that both fasted and fed concentrations would be lower in dogs with gastrointestinal disease. Short-term GLP-2 responses were compared in dogs with chronic enteropathies one month after starting treatment for their disease, with the hypothesis that GLP-2 concentrations would increase concurrent with clinical disease response. Eighteen client-owned dogs with chronic enteropathies were enrolled prior to targeted therapy for gastrointestinal disease. Seventeen healthy client-owned dogs were enrolled as a control group. In all dogs, fasted blood samples were obtained, followed by samples 1 and 3 hours after feeding a standardized meal. Blood was collected into chilled EDTA tubes, and two proteinase inhibitors were added to the sample at the time of collection. Samples were immediately centrifuged, plasma separated, and frozen (-80°C). Same-day fecal samples were collected and scored using a previously established fecal scoring system. Standardized, previously established scoring systems for canine chronic enteropathies were used to score disease severity. All procedures were repeated 30 days following enrollment in the chronic enteropathy population. Plasma GLP-2 concentrations were measured using a canine-specific ELISA. A mixed-effects analysis accounting for repeated measures was used to compare post-prandial GLP-2 changes in all dogs. A mixed analysis of variance, accounting for repeated measures, within-subject effects, and between-subject effects, was used to analyze effects of study day or study group on GLP-2 concentrations. Fasted and post-prandial plasma GLP-2 concentrations were lower in dogs with uncontrolled gastrointestinal disease compared to healthy dogs at the time of diagnosis (P < 0.0001) and at study follow-up (P < 0.001). Post-prandial GLP-2 concentrations were higher at the 1-hour post-prandial time-point at study recheck compared to enrollment in CE dogs (P = 0.02). The results of this study suggest altered enteroendocrine responses, specifically decreased GLP-2 secretion, in dogs with chronic enteropathies compared to healthy dogs. Treatment for gastrointestinal disease may help to normalize GLP-2 response.
Keywords: Enteroendocrine; Enteropathies; Gastrointestinal; Glucagon-like peptide-2; Inflammatory bowel disease